2004
DOI: 10.1111/j.1365-2036.2004.02288.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyteaphaeresis in steroid‐dependent inflammatory bowel disease: a prospective, open, pilot study

Abstract: Summary Background : Uncontrolled studies suggest that granulocyteaphaeresis might be useful in the management of active ulcerative colitis. Aim : To assess the efficacy of granulocyteaphaeresis treatment in active steroid‐dependent inflammatory bowel disease. Methods : We conducted a multicentre, prospective, open, pilot study in patients with steroid‐dependent inflammatory bowel disease. All patients were started on 60 mg/day of prednisone; after 1 week, a five‐session programme of granulocyteaphaeresis (onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
2
8

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 31 publications
7
64
2
8
Order By: Relevance
“…Furthermore, all responding patients but one completed a one year long-term follow up without requiring steroids or the introduction of any other therapy. These results are in keeping with the findings reported by Domenech et al [8] and support the steroid sparing effect of GCAP in steroid dependent UC patients. Interestingly, steroid consumption in our study was lower in group 2, showing statistically significant difference in a period starting when group 1 patients were no longer receiving aphaeresis treatment, and group 2 was still under active aphaeresis treatment.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, all responding patients but one completed a one year long-term follow up without requiring steroids or the introduction of any other therapy. These results are in keeping with the findings reported by Domenech et al [8] and support the steroid sparing effect of GCAP in steroid dependent UC patients. Interestingly, steroid consumption in our study was lower in group 2, showing statistically significant difference in a period starting when group 1 patients were no longer receiving aphaeresis treatment, and group 2 was still under active aphaeresis treatment.…”
Section: Discussionsupporting
confidence: 83%
“…Reducing granulocytes and monocytes by apheresis has the potential to reduce bowel inflammation and to improve patient status. Several controlled and uncontrolled studies have assessed the safety and efficacy of granulocyteaphaeresis (GCAP) in steroid-dependent UC [5][6][7][8] , steroid-refractory UC [9][10][11] , or as first-line therapy in naïve UC patients [12,13] . However, the optimal treatment scheme is still to be established.…”
Section: Introductionmentioning
confidence: 99%
“…However, steroid administration can increase susceptibility to infections, diabetes mellitus and osteoporosis. Recently, it was reported that steroidrefractory or steroid-dependent patients with UC can be effectively treated by cytapheresis [7][8][9][10] . To determine whether leukocytapheresis (LCAP) may also be useful with other UC patients, we administered LCAP to 18 steroid-naive UC patients.…”
Section: Introductionmentioning
confidence: 99%
“…En nuestro país, Doménech y cols. realizaron un estudio multicéntrico prospectivo incluyendo a 14 pacientes con CU corticodependiente a los que al inicio de las sesiones de GCAF (5 sesiones en 5 semanas) se administraba una dosis inicial de 60 mg de prednisona con reducción semanal de 10 mg de la dosis de corticoides, comprobando una remisión clínica en el 60% de los pacientes a 6 semanas con reducción en la dosis de esteroides en el 90% y mantenimiento de la remisión en el 75% de los respondedores tras 12,6 meses de seguimiento (11). En CU corticorrefractaria merece la pena comentar el estudio más amplio en cuanto a pacientes, llevado a cabo por Hanai y cols.…”
Section: Discussionunclassified